Optimization of the Role of BAZNAS KCP Sumenep in Zakat Management for Local Community Empowerment - Buchari, Imam; Fuadah, Irma Wardatul; Sulalah, Sulalah; Munawwaroh, Aulia Datul (Yayasan Rahmat Islamiyah, 2025)
This study analyzes the optimization of BAZNAS KCP Sumenep’s role in zakat management for local community empowerment. Using a qualitative research method, this study examines strategies for zakat collection, distribution, and utilization in addressing geographical challenges, low zakat literacy, and limited infrastructure. The findings indicate that digitalization innovation, increased transparency, and strengthened stakeholder collaboration are key to optimizing zakat management. These findings are expected to serve as a reference for more effective zakat policies in poverty alleviation.